UPAYA MENINGKATKAN HASIL BELAJAR SISWA TENTANG PESAN MELALUI TELEPON DENGAN METODE PEMODELAN SISWA KELAS IV SD NEGERI 111 PEKANBARU - Artuti (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Low student learning outcomes are due to a less precise selection of learning methods that suit the subject matter presented to the students. Efforts to overcome this necessitate a method or a proper way so that every student is able to receive information in every lesson well. Stages for easy entry of information include listening, writing or drawing, and then viewing and conducting their own experiments. To address this, the researchers conducted classroom action research by applying methods of modeling. The subjects were fourth-grade students of SD Negeri 111 Pekanbaru with a total of 30 students. This research was conducted over 2 cycles. Data collection techniques used were observation of the activities of teachers and students, and achievement tests.Research suggests that the application of modeling methods can improve learning outcomes in Indonesian language, specifically on the material of conveying a message over the phone. This is evidenced by: (a) an increase in the activity of the teacher. In the first cycle, the first meeting obtained a "sufficient" category with a score of 35 (58.33%). At the second meeting of the first cycle, a "good" category was earned with a score of 43 (71.67%). In the first meeting of Cycle II, a "good" category was obtained with a score of 49 (81.67%). At the second meeting of the second cycle, activity students gained a "Very Good" category with a score of 53 (88.33%). Besides the activities of students, in the first cycle, the first meeting obtained a score of 34 (56.67%) with a "sufficient" category. At the second meeting of the first cycle, a score of 46 (76.67%) was obtained with a "good" category. In the first meeting of Cycle II, a score of 51 (85.00%) was obtained, leading to the category of "Very Good." At the second meeting of the second cycle, activity students obtained a score of 57 (95.00%), resulting in a "Very Good" category; and (b) learning outcomes have increased. On the basis of scores obtained, an average value of 48.38 was achieved, placing it in a "low" category. In the first cycle, an average value of 72.00 was obtained, resulting in a "high" category. In the second cycle, an average value of 76.50 was earned, placing it in the "high" category. Mastery learning of individual students in each cycle has increased. On the basis of completeness scores, individual students obtained a score of 36.67% (11 students). At the first cycle, a score of 60.00% (18 students) was obtained. In the second cycle, this increased with the acquisition of a score of 86.67% (26 students).